Farm Animal Proteomics 2013 2013
DOI: 10.3920/978-90-8686-776-9_38
|View full text |Cite
|
Sign up to set email alerts
|

The effect of microbial challenge on the intestinal proteome of broiler chickens

Abstract: Background: In poultry production intestinal health and function is paramount to achieving efficient feed utilisation and growth. Uncovering the localised molecular mechanisms that occur during the early and important periods of growth that allow birds to grow optimally is important for this species. The exposure of young chicks to used litter from older flocks, containing mixed microbial populations, is a widely utilised model in poultry research. It rarely causes mortality but effects an immunogenic stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This could be related to the fact that treatments normalised the moisture in the different bedding materials, allowing the litter microbiota to be kept under control. These findings also agree with the non-significant differences found regarding the intestinal traits and the productive parameters at the end of the rearing period, which are suggestive of inexistence of an environmental bacterial challenge (O'Reilly et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…This could be related to the fact that treatments normalised the moisture in the different bedding materials, allowing the litter microbiota to be kept under control. These findings also agree with the non-significant differences found regarding the intestinal traits and the productive parameters at the end of the rearing period, which are suggestive of inexistence of an environmental bacterial challenge (O'Reilly et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…For AGP, the changes over time were not as variable as the other APP, a significant difference only observed between days 17 and 20 in the modern line ( P = <0.05). Previous work suggests that there is a normal increase in AGP concentration over the early period of growth with significant increases over time between days 12 and 22 (O’Reilly, 2013 ), though studies focusing on AGP between 3 and 7 wk of age found AGP not to be affected age (Inoue et al, 1997 ).…”
Section: Resultsmentioning
confidence: 99%